wMel Wolbachia alters female post-mating behaviors and physiology in the dengue vector mosquito Aedes aegypti (2023)
ABSTRACT: Globally invasive Aedes aegypti disseminate numerous arboviruses that impact human health. One promising method to control Ae. aegypti populations is transinfection with Wolbachia pipientis, which naturally infects ~40–52% of insects but not Ae. aegypti. Transinfection of Ae. aegypti with the wMel Wolbachia strain induces cytoplasmic incompatibility (CI), allows infected individuals to invade native populations, and inhibits transmission of medically relevant arboviruses by females. Female insects undergo post-mating physiological and behavioral changes—referred to as the female post-mating response (PMR)—required for optimal fertility. PMRs are typically elicited by male seminal fluid proteins (SFPs) transferred with sperm during mating but can be modified by other factors, including microbiome composition. Wolbachia has modest effects on Ae. aegypti fertility, but its influence on other PMRs is unknown. Here, we show that Wolbachia influences female fecundity, fertility, and remating incidence and significantly extends the longevity of virgin females. Using proteomic methods to examine the seminal proteome of infected males, we found that Wolbachia moderately affects SFP composition. However, we identified 125 paternally transferred Wolbachia proteins, but the CI factor proteins (Cifs) were not among them. Our findings indicate that Wolbachia infection of Ae. aegypti alters female PMRs, potentially influencing control programs that utilize Wolbachia-infected individuals.